Developing a metadata best practices model: the experience of the Colorado State University Libraries - Hunter, Nancy, author; Liu, Shu, author; Rettig, Patricia J., author; Level, Allison V., author; The Haworh Press, Inc., publisher (Colorado State University. Libraries, 2008)
The Metadata Best Practices Task Force at the Colorado State University (CSU) Libraries developed a core set of metadata elements and an accompanying data dictionary to facilitate a coordinated metadata management approach for a central digital repository of diverse digital objects. This article describes the rationale for the Task Force and the process used for its work following a look at the background of digitization and past metadata practices at CSU. The article includes a literature review on institutional metadata projects and examples, and it ends with a description of the Task Force's ongoing work and plans for future assessment.
Final, peer-reviewed manuscript.
Keywords: Colorado State University. Libraries; Colorado State University. Libraries. Metadata Best Practices Task Force; Metadata -- Colorado -- Fort Collins; Institutional repositories -- Colorado -- Fort Collins; Digital libraries -- Colorado -- Fort Collins; Data dictionaries -- Colorado -- Fort Collins